A Cross-Sectional Survey on Knowledge and Awareness of Digital Dentistry in Prosthodontics Among Interns and Postgraduates of Dental Colleges in Mumbai and Navi Mumbai - Saurabh Sarode; Vishwas Kharsan; Gauri Phansalkar; Harshit Agarwal; Ankush Jadhav; Priyanka Chaugule (Ann Publisher, 2026)
Background. Digital dentistry is increasingly integrated into prosthodontic practice, but training opportunities for dental trainees may vary. Aims. This study assessed awareness, educational exposure, hands-on experience, perceived curriculum adequacy, and barriers to implementation. Methods. A cross-sectional survey was conducted among interns and postgraduate students using a self-constructed, validated questionnaire. The questionnaire covered awareness of digital dentistry, attendance at lectures/workshops, undergraduate curricular exposure, exposure to specific digital technologies, hands-on use and tools used, perceived adequacy of curricular training, attitudes toward curriculum expansion, primary knowledge sources, perceived barriers, and expected future impact. Data were summarized as n (%) and compared between postgraduates and interns using Chi-square or Fisher’s exact tests. Results. A total of 100 responses were analyzed (51 postgraduates, 49 interns). Awareness was high (98% had heard of digital dentistry; 89% knew prosthodontic applications). Workshop/lecture attendance was 43%, higher among postgraduates than interns (p<0.001), while undergraduate curricular exposure was 31%. Reported exposure was highest for scanners (85%), CAD/CAM (81%), and digital impression systems (77%). Hands-on experience in prosthodontics was reported by 40%, more often among postgraduates than interns (p<0.001), with intraoral scanners most commonly used. Only 17% felt curricular training was sufficient, and most supported adding more digital dentistry content. Online resources were the most common knowledge source (50%), and cost/financial issues were the most reported barrier (46%). Conclusion. Trainees showed strong awareness and positive attitudes toward digital dentistry, but practical exposure and perceived curriculum adequacy were limited. Structured hands-on training and resource support may help bridge this gap.